KARAKTERISTIK ENDAPAN DANAU RAWA PENING DI MUARA INLET SUNGAI GALEH, KECAMATAN AMBARAWA, KABUPATEN SEMARANG - Muhammad Fikri Abubakar; Setyo Pambudi (KURVATEK, 2020)
The Galeh River inlet estuary on Lake Rawa Pening is located in Ambarawa District, Semarang Regency. Sampling of Rawa Pening sediment at two points using modern coring methods. The coring results were observed and granulometric analysis was done using lazer scanning method with Master Sizer 2000. Core RWP-01 samples in the form of fine clastic sediments (Sand-Silt), reflecting the inlet river estuary environment in the hydrological lake system which is influenced by the fluvio-lacustrin process and showing characterizer of shallow lake facies. RWP-02 core samples in the form of fine-textured sediments (mud) rich in organic material, reflecting a relatively calm and stable depositional environment, formed by the density current mechanism that characterize the deep lake facies. The development of these sedimentary characters shows changes in sedimentary facies, namely shallow lake facies developing into clastical lake lacustrine into deep lake lacustrine facies.